Time structuring of media communication: differential approach - Abanina, H. (Університет «КРОК», 2018)
The results of theoretical and methodological analysis of the problem of media communication time structuring are shown in context of differential approach. The term of individual temporal style is proposed. The criteria of typologizing of different style features (conscious self-regulation, time perspective, emotional characteristics of time perception) are defi ned and characterized. In accordance with the highlighted criteria the theoretical typology construct is developed, which includes temporally-autonomous, situationally-active, contemplative and temporally-spontaneous styles

Представлено результати теоретико-методологічного аналізу проблеми структурування часу медіакомунікації в контексті диференціального підходу. Запропоновано поняття індивідуального темпорального стилю. Визначено та охарактеризовано критерії типологізації стильових особливостей організації часу медіакомунікації (усвідомлена саморегуляція, часова перспектива, емоційні характеристики переживання часу). Відповідно до виділених критеріїв розроблено теоретичний конструкт типології темпоральних стилів, який включає темпоральноавтономний, ситуативно-активний, споглядально-пасивний і темпорально-стихійний стилі.
Keywords: time structuring; media communication; individual temporal style; self-regulation; time perspective; структурування часу; медіакомунікація; індивідуальний темпоральний стиль; саморегуляція; часова перспектива